Spatial and seasonal variations of major and trace elements in Antarctic seawater. Chemometric investigation of variable and site correlations - ABOLLINO, Ornella; ACETO, Maurizio; LA GIOIA, Carmela; SARZANINI, Corrado; MENTASTI, Edoardo (2001)
The concentrations of fourteen elements in seawater collected during the 1994-95 and 1995-96 Italian expeditions to Antarctica were determined by stripping voltammetry or atomic spectroscopy. The results obtained are discussed as a function of the sampling period and location. Heavy metal concentrations for samples collected during the 1993-94 campaign are also reported. Dissolved levels of major, minor and trace elements were found to decrease after pack ice melting because of water dilution and bioaccumulation, the latter being particularly relevant for heavy metal concentrations. The elaboration by chemometric multivariate techniques allowed identification of two groups of samples, respectively, collected before and after pack ice melting, and to find correlations among variables, such as alkaline-earth metals.